CANCER REHABILITATION AND THE FUNCTIONAL OUTCOMES : A SYSTEMATIC REVIEW - Prasetyo, Rosyid; Nuswantoro, Yoga Nuswantoro; Anggraini, Efa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Cancer rehabilitation is a subspecialty of rehabilitation medicine concerned with restoring and maintaining the highest possible level of function, independence, and quality of life to patients at all stages of their cancer diagnosis, including those undergoing potentially curative therapy, those receiving palliative care, and cancer survivors. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 961 articles, whereas the results of our search on SCIENCE DIRECT brought up 211 articles. The results of the search conducted for the last year of 2014 yielded a total 45 articles for PubMed and 34 articles for SCIENCE DIRECT. In the end, we compiled a total of  6 papers, 5 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included six research that met the criteria. Conclusion: In summary, these findings give evidence that rehabilitative therapies are effective for people who have had cancer. The findings should be considered in light of the fact that several studies exhibited a moderate risk of bias and/or limitations in research quality. These findings may serve as a platform for future research aimed at developing clinical practice guidelines for rehabilitative therapies across cancer types.